INTEGRATIVE CURRICULUM DEVELOPMENT BASED ON HIGHER ORDER THINKING SKILLS (HOTS) IN PRIMARY EDUCATION - Fuad Hasan (STIT Pringsewu, 2025)
This study examines the development of an integrative curriculum and its role in embedding Higher Order Thinking Skills (HOTS) in primary education. Through a systematic literature review, this research finds that an integrative curriculum facilitates holistic learning by connecting various subjects to real-world contexts. Effective pedagogical strategies, such as project-based learning, inquiry-based learning, and contextualized problem-solving, are proven to enhance students' cognitive abilities, including critical thinking, creativity, and problem-solving. Nevertheless, implementation faces challenges, such as a lack of teacher readiness, resource limitations, and policy alignment issues. An integrative curriculum focused on HOTS is crucial for preparing students to be lifelong learners and global citizens..